2023
DOI: 10.1007/s00415-022-11545-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-visual hallucinations in Parkinson’s disease: a systematic review

Abstract: Background Non-visual hallucinations in Parkinson’s disease (PD) can be prevalent and distressing. Most existing research has however, focused on visual hallucinations as well as related risk factors. The current study thus conducted a systematic review to collate existing evidence on non-visual hallucinations in PD, focusing on their prevalence, phenomenology, and clinical-cognitive correlates. Methods Ninety-one relevant studies were included from a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…OHs have been frequently studied in the context of psychiatric disorders or neurological conditions due to epilepsy or COVID-19 infection, while their features in PD are less understood [ 13 , 14 , 15 ]. Among non-visual hallucinations, OHs may frequently occur in PD patients, but they are often overlooked in clinical practice [ 47 ]. Moreover, clinicians should always check for phantosmia during the disease’s clinical course, not just at the baseline assessment, as longitudinal studies have identified phantosmia in initially unaffected PD patients [ 32 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…OHs have been frequently studied in the context of psychiatric disorders or neurological conditions due to epilepsy or COVID-19 infection, while their features in PD are less understood [ 13 , 14 , 15 ]. Among non-visual hallucinations, OHs may frequently occur in PD patients, but they are often overlooked in clinical practice [ 47 ]. Moreover, clinicians should always check for phantosmia during the disease’s clinical course, not just at the baseline assessment, as longitudinal studies have identified phantosmia in initially unaffected PD patients [ 32 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral sensory hallucinations (OSHs), referred to as oral cenesthopathy, are psychiatric symptoms predominantly observed in older individuals 1 . Nonvisual hallucinations, including OSHs, have been identified as clinical features that have potential to support the diagnosis of Parkinson's disease (PD) and dementia with Lewy bodies (DLB) 2,3 . Since individuals with PD/DLB have alterations in the dopaminergic system due to alpha‐synucleinopathy, 3,4 research suggests that OSHs may also be linked to these alterations 3–5 .…”
Section: Figurementioning
confidence: 99%
“… 1 Nonvisual hallucinations, including OSHs, have been identified as clinical features that have potential to support the diagnosis of Parkinson's disease (PD) and dementia with Lewy bodies (DLB). 2 , 3 Since individuals with PD/DLB have alterations in the dopaminergic system due to alpha‐synucleinopathy, 3 , 4 research suggests that OSHs may also be linked to these alterations. 3 , 4 , 5 However, the underlying pathophysiology of OSHs remains unclear.…”
mentioning
confidence: 99%
“…In PD, hyposmia is one of the first non-motor signs of the disease [28,30,31], and olfactory hallucinations (phantosmia) are reported in up to 21% of cases [32]. In addition, the olfactory threshold has been proposed as a test to differentiate Lewy bodies dementia (LBD) from Parkinson's dementia, as patients with LBD have a much lower olfactory threshold [33].…”
mentioning
confidence: 99%